Differences in gender and outcomes following isolated coronary artery bypass graft (CABG) surgery - Roxana Sadeghi; Reza Miri; Naser Kachoueian; Mohammad Sistanizad; Rezvan Hassanpour (ARYA Atherosclerosis, 2023)
Background: Gender impacts pre-, intra-, and postoperative parameters and outcomes following coronary artery bypass graft (CABG) with conflicting results. This study aimed to identify differences in preoperative, intraoperative, and postoperative parameters. It also seeks to compare the postoperative complications and mortality between two genders who had CABG surgery. Methods: This prospective observational study included patients who had isolated CABG and were divided based on gender. Demographic information, underlying comorbidities, drug history, clinical and laboratory data at the time of referral, operative characteristics, postoperative variables, and mortality outcomes were tracked during hospitalization and six months after discharge. Results: Three hundred twenty patients were enrolled in the study during its duration. 71% were male. Women were older (62.40±9.03 vs. 59.99±9.81 years, p= 0.011) and had more dyslipidemia (p=0.003), hypertension (p=0.000), and diabetes (p=0.001), whereas men admitted with more myocardial infarction (MI) (p=0.011) and had lower Ejection fraction (EF) (p=0.001). They also had lower EF post-surgery and six months after discharge (p <0.001, 0.006). However, the number of vessels involved was not different between genders (p=0.589), but the number of grafts was higher in men (p=0.008).There was no statistically significant difference in overall mortality rates between the two groups (4.42% and 6.38% in men and women, respectively, p= 0.464).Conclusions: The women had more underlying comorbidities than men. Furthermore, there were some differences in the intra-operative parameters and postoperative complications between the two genders, but there was no difference in postoperative mortality in our setting.